The Impact of Social Media on Political Activism – A Comparative Analysis - Jain, Ansh; Teckchandani, Jyotika (International Journal of Research in Interdisciplinary Studies, 2023)
This paper presents a relative examination of the effect of virtual entertainment on political activism across various settings. Drawing on existing writing and contextual analyses, it analyzes the benefits and drawbacks of virtual entertainment in assembling people, arranging efforts, enhancing voices, bypassing government constraint, and encouraging worldwide fortitude. The examination features the complicated elements at play, remembering the job of virtual entertainment for dispersing data, working with on the web and disconnected activism, and molding political talk. By investigating these elements, the paper offers bits of knowledge into the multi-layered connection between web-based entertainment and political activism, underlining the requirement for a nuanced comprehension of its suggestions for majority rule interest and social change.